To determine which of the given equations has exactly the same solutions as \((x−7)(x+9)=0\), we first need to find the solutions of the original equation.
Setting \((x−7)(x+9)=0\) gives us:
- \(x - 7 = 0 \implies x = 7\)
- \(x + 9 = 0 \implies x = -9\)
So the solutions are \(x = 7\) and \(x = -9\).
Now, we need to check each of the given options to see which one has the same solutions.
-
\(x^2 - 2x - 63 = 0\)
We can factor or use the quadratic formula to find the roots: \[ x^2 - 2x - 63 = (x - 9)(x + 7) = 0 \] Thus, the solutions are \(x = 9\) and \(x = -7\). Not the same. -
\(x^2 = -2x + 63\)
Rearranging gives: \[ x^2 + 2x - 63 = 0 \] Factoring: \[ (x - 7)(x + 9) = 0 \] So the solutions are \(x = 7\) and \(x = -9\). This one matches! -
\(x^2 = 2x - 63\)
Rearranging gives: \[ x^2 - 2x + 63 = 0 \] This doesn’t factor nicely and has different roots. Not the same. -
\(x^2 + 2x = -63\)
Rearranging gives: \[ x^2 + 2x + 63 = 0 \] This also doesn’t yield the same solutions upon solving.
After checking all the equations, the one that has exactly the same solutions as \((x−7)(x+9)=0\) is:
\(x^2 = -2x + 63\).